CASE STUDY: THE USE OF METCOVAZIN IN CURING BURNS - Irnawati, Irnawati (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2019)
Burn is the most common trauma for kids happens due to contact with fire, hot objects, electricity, and chemicals. The size, location, and depth of burn become the main factor that affect the curing treatment. Complications, such as; infection, toxic shock syndrome, scar, and psychological symptoms, can be occurred if the wound did not treat in a good and proper way. This study aimed to describe the use of metcovazin® and management treatment on two cases of second-degree burns. The principle of TIME (Tissue management, Inflammation & Infection control, Moisture balance, Edge) as the modern dressing used for wound management treatment. The result showed that using TIME management treatment could quicken the healing process of the wound. It was able to increase basic defense of a healthy wound. The combination of metcovazin® and modern dressing were effective in curing the second-degree burns.